MAKSIM CARA BAHASA JAWA DALAM TRANSAKSI JUAL BELI DI PASAR PELITA SK 17 KABUPATEN TANJUNG JABUNG TIMUR - Endang Puji Rahayu; Hary Soedarto Harjono (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2016)
ABSTRACT The purpose of this research is to analyze and describe the Compliance and irregularities Maksim How Java language in the Sale and Purchase Transactions in the Market Pelita SK 17 village Bangun Karya Tanjung Jabung Timur. The approach in this study is a qualitative approach. Penlitian type is descriptive. Results from this study indicate that the Compliance maxims in Javanese way between sellers and buyers in the market lamp SK 17 village Bangun Karya Tanjung Jabung Timur. In the context of sale and purchase transactions speech salted fish, fish, vegetables, and spices, as well as offering vegetables, and offers fish. Speakers do not adhere to the maxim of the way for providing information that is unclear, confusing and ambiguous. In the context of the narrative of buying and selling chicken, fish, clothes, and know, and wares. Key words: maxim way, the Java language